MODERNIZATION IN FILM AND THEATRE: A SYNTHESIS OF TRADITIONAL AND MODERN STYLES - Ochilova Kamola Ilkhom kizi (Sciental Journals Publishing, 2025)
This article analyzes the processes of integration of traditional and modern styles in the cinema and theater of Uzbekistan. These processes, which began in the post-independence period, served to improve the quality of art and expand its opportunities for recognition in the international arena. The article examines in depth how traditional and modern elements are synthesized, how this synthesis affects the expressive capabilities of works of art and how it can contribute to overall cultural development. The significance of this synthesis process for future scientific research and development directions is also discussed.
Keywords: Uzbekistan, cinema, theater, modernization, traditional styles, modern styles, synthesis, cultural development, international recognition, art studies.